2019
DOI: 10.1136/bmjopen-2018-028777
|View full text |Cite
|
Sign up to set email alerts
|

Minimal important differences for improvement in shoulder condition patient-reported outcomes: a systematic review to inform aBMJRapid Recommendation

Abstract: ObjectivesTo identify credible anchor-based minimal important differences (MIDs) for patient-reported outcome measures (PROMs) relevant to aBMJRapid Recommendations addressing subacromial decompression surgery for shoulder pain.DesignSystematic review.Outcome measuresEstimates of anchor-based MIDs, and their credibility, for PROMs judged by the parallelBMJRapid Recommendations panel as important for informing their recommendation (pain, function and health-related quality of life (HRQoL)).Data sourcesMEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 56 publications
4
97
2
1
Order By: Relevance
“…We have not established the validity of our instrument by formal testing. In other work, however, we have shown that the current criteria for credibility succeed in partially explaining the variability in the magnitude of the MID 2993. Our instrument does not deal with the underlying measurement properties of the patient reported outcome measures (that is, validity and responsiveness) and assumes that users will only move forward in evaluating the credibility of MIDs if the instrument has met at least minimal standards of validity and responsiveness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have not established the validity of our instrument by formal testing. In other work, however, we have shown that the current criteria for credibility succeed in partially explaining the variability in the magnitude of the MID 2993. Our instrument does not deal with the underlying measurement properties of the patient reported outcome measures (that is, validity and responsiveness) and assumes that users will only move forward in evaluating the credibility of MIDs if the instrument has met at least minimal standards of validity and responsiveness.…”
Section: Discussionmentioning
confidence: 97%
“…In developing our inventory of anchor based MIDs, and in other related work,2993 we found that the literature often includes a number of candidate MIDs for the same patient reported outcome measure. Moreover, the magnitude of these estimates sometimes varies widely.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant reduction (4 vs. 1, 30% drop form baseline) in pain intensity was observed only in the NS group, while the traditional MSS group remained essentially stable. A 30-35% reduction in pain from baseline or a decrease of 1.5 to 1.6 on a 10-point NPRS can be considered significant and was rated as MCID (believed to be meaningful by the patients) (42)(43)(44). Previous research showed symptoms (pain) relief after stretching program in athletes with GIRD and impingement-related shoulder pain (45).…”
Section: Pain and Satisfaction Levelmentioning
confidence: 99%
“…However, a signi cant reduction (4 vs. 1, 30% drop form baseline) in pain intensity was observed only in the NS group, while the traditional MSS group remained essentially stable. A 30-35% reduction in pain from baseline or a decrease of 1.5 to 1.6 on a 10point NPRS can be considered signi cant and was rated as MCID (believed to be meaningful by the patients) (42)(43)(44). Previous research showed symptoms (pain) relief after stretching program in athletes with GIRD and impingement-related shoulder pain (45).…”
Section: Pain and Satisfaction Levelmentioning
confidence: 99%